Comparative Study of Psychological Distress Profile and Maladaptive Personality Dimensions (PID-5) Among Victim and Persecutor Individuals Referring to Domestic Violence Problem in Social Emergency (123) - Karim Babaei; Marziyeh Sattari; Saeedeh Noor Mohammadi Ahari (Fasa University of Medical Sciences, 2020)
Background & Objective: domestic violence is a type of social harm that can have adverse effects on different aspects of human life, of which the most important ones can be psychological outcomes such as depression and anxiety that can cost a lot to both the individual and the community. The purpose of this study was to compare the psychological distress profile and maladaptive personality dimensions (PID-5) among the victim and persecutor people referring to the problem of spouse abuse in the social emergency. Materials & Methods: The method of this research is causal-comparative study. The statistical population of this study included all participants who referred to the social emergency with the problem of spouse abuse in 2018. Sixty couples were selected through Purposive sampling. Data were collected by Personality Inventory for DSM-5 [PID-5], Depression, Anxiety and Stress Scale (Dass-21) and the standard questionnaire on violence against women. Data were analyzed using descriptive indicators and Multivariate and univariate analysis of variance. Results: The results showed that victim dimension in personality, negative affect and dimensions of psychological distress profile, including anxiety and stress, experienced high levels of Persecutor, but this difference was significant but in other dimensions there was no significant difference, as well as Persecutor in Personality dimensions include Antagonism, and Disinhibiting of higher levels of experience, which is significant between the two groups. Conclusion: The findings of this study indicate that the education and treatment of these subjects can by recognition and diagnosis some of the clinical problems and maladaptive personality traits in the victim and Persecutor people.